PENGARUH PENILAIAN KOMITMEN PROFESIONAL DAN PEMBELAJARAN ETIKA PROFESI AKUNTANSI TERHADAP PERSEPSI ETIS PADA MAHASISWA - Alif Fahtur Rohman; Rochmawati Rochmawati (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
S1 students of the Accounting Study Program and Accounting Education class of 2020 at Surabaya State University have ethical perceptions when analyzing accountants' professional ethics cases. Supporting a career as a professional accountant candidate requires professional commitment, learning good professional ethics in the work environment, and also supporting the social life of the community. The research method used in this study is quantitative. The population used in this study is students of the accounting and accounting education study program at Surabaya State University in 2020. The analysis technique used in this study is multiple linear regression analysis using SPSS. The results of this study have a have a sig value of < 0.05, which is 0.000 < 0.05, so this study has a viable model. It can be said that the independent variables of assessment of professional commitment and learning of accounting professional ethics have an effect simultaneously or together on students' ethical perceptions. The significance of t < the value of sig. 0.05 or 0.001 < 0.05. so it can be concluded that H0 is rejected and H1 is accepted, which means that the Professional Commitment Assessment has a positive and significant effect on students' ethical perceptions. The significance of t > the value of sig. 0.05 or 0.085 > 0.05. so it can be concluded that H0 is accepted and H1 is rejected, which means that Learning Accounting Professional Ethics has a positive but insignificant effect on students' ethical perceptions.